1998
DOI: 10.1021/jp9733476
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Double-Pulse Excitation Study of α-Sexithienyl Film

Abstract: Relaxation dynamics from a higher triplet excited state in R-sexithienyl (hereafter abbreviated as 6T) film was investigated by double-pulse excitation spectroscopy. Very rapid formation (within 1 ps) of the lowest singlet excited state and an intermolecular ion-pair state were observed. The mechanism of this rapid conversion process from a higher electronic excited state was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…However, an intense shoulder is observed near 25 000 cm -1 , suggesting that more disorder is probably present in the solid state. These spectral properties have been reported in the literature for QT 16,22 and for other unsubstituted oligothiophenes , ,, and have been well explained using the excitonic model, which predicts a splitting in the absorption spectra. The excitonic model has been fully described by Kasha .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…However, an intense shoulder is observed near 25 000 cm -1 , suggesting that more disorder is probably present in the solid state. These spectral properties have been reported in the literature for QT 16,22 and for other unsubstituted oligothiophenes , ,, and have been well explained using the excitonic model, which predicts a splitting in the absorption spectra. The excitonic model has been fully described by Kasha .…”
Section: Resultssupporting
confidence: 76%
“…These studies have also allowed us to obtain a good correlation between the presence (or not) of thermochromism for the substituted polythiophenes and the conformation and rotational barriers of the repetitive units found in the polymer backbone . The spectroscopic properties of unsubstituted oligothiophenes in the solid state (specially the tetramer and the hexamer) have been widely studied in the literature. From these results, a better understanding of the effect of intermolecular interactions on the optical properties of these molecules has been achieved. It has been found that the intermolecular interactions present in the solid state cause a Davydov splitting (excitonic splitting) in the absorption spectra of unsubstituted thiophene oligomers.…”
Section: Introductionmentioning
confidence: 97%
“…The resultant picosecond PM spectra are dramatically different from those previously measured in thin polycrystalline ␣6T films. 22,23 First, a pronounced short-lived PA band ͑band A͒ is observed at បϭ1.25 eV in the LT crystal and at បϭ1.3 eV in the HT crystal phase. This band is usually not observed in polycrystalline films.…”
Section: A Femtosecond and Picosecond Photomodulationmentioning
confidence: 99%
“…20 Therefore, it is not surprising that the transient PM spectra of ␣6T crystals dramatically differ from those of ␣6T films. 22,23 The ultrafast dynamics in films are governed by exciton trapping at numerous defects, most of which act as deep traps. As a result, it is impossible to measure the intrinsic PM spectrum of free Frenkel excitons.…”
Section: A Femtosecond and Picosecond Photomodulationmentioning
confidence: 99%
See 1 more Smart Citation